El relativismo y el valor de la vida humana: extractos de “Fratelli Tutti” del Papa Francisco - Lafferriere, Jorge Nicolás (2025)
Fil: Lafferrière, Jorge Nicolás. Pontificia Universidad Católica Argentina; Argentina